Pengaruh PAD Dan DAU Terhadap Belanja Langsung (Studi Pada Kabupaten/Kota Di Provinsi Jawa Tengah) - Dhiah Novita; Ayunda Putri Nilasari (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2021)
This research aims to determine the effect of local revenue and general allocation funds on direct expenditures in districts/cities of Central Java Province. The research method used is the classical assumption test, multiple linear regression analysis, and the coefficient of determination test. The results showed that partially the local original income and general allocation funds variables affected direct expenditure in districts/cities of Central Java Province. Simultaneously, the variables of local revenue and general allocation funds have an effect on direct spending in districts/cities of Central Java Province.